Development of academic achievement on inventories Using the project as a base of 3rd year vocational certificate students, Khunhan Vocational College - Saengaroon, Ketwadee (Academic Journal of Local Development, 2024)
The purpose of this research is to develop academic achievement in the subject Inventories Using the project as a base of 3rd year Vocational Certificate level students at Khunhan Vocational College to compare academic achievement between before and after study. Re: Inventories Using the project as a base of 3rd year Vocational Diploma students at Khunhan Vocational College to develop academic achievement in the subject of inventories to be effective according to the specified criteria 80/80 and to study satisfaction with learning about Inventories Using the project as a base of 3rd year vocational certificate students, Khunhan Vocational College There are a total of 10 target groups, 3rd year Vocational Diploma students, Khunhan Vocational College. This research used 4 types of research tools: 6 learning plans, a pre-class test, skill practice exercises, and a satisfaction questionnaire. Statistics used in data analysis are divided into 3 types: 1) Basic statistics used in data analysis include percentage, mean, standard deviation, etc. 2) Comparative statistics used in data analysis include t-test Dependent. 3) Statistical analysis of the effectiveness of academic achievement in the subject Inventories Using the project as a base, using the E1/E2 criteria to analyze the data. The research results found that Achievement in learning about Inventories Using the project as a base of 3rd year vocational certificate students, Khunhan Vocational College The average overall pre-test score was 46.66. The average overall post-test score was 82.91. The pre-test and post-test scores developed differently. It was found that students had higher academic achievement after studying than before studying. Comparison of academic achievement between before studying and after studying about inventories. Using the project as a base of 3rd year vocational certificate students, Khunhan Vocational College The average overall pre-test score was 9.33. The average overall post-test score was 16.58. The t-test value = 40.40, showing that the created innovation increased student learning with the pre-test and post-test scores being significantly different. Statistical significance at the 0.5 level Organizing teaching and learning about inventories using a project as a base. of 3rd year vocational certificate students, Khunhan Vocational College To be effective according to the specified criteria of 80/80, it was found that the efficiency was equal to 82.50/82.91 compared to the criteria of 80/80. It shows that teaching and learning about inventories is based on projects. of 3rd year vocational certificate students, Khunhan Vocational College The researcher took the scores during the project-based study (E1) and compared them with the scores after taking the learning achievement test. Inventories (E2) found that the project Inventories It has an efficiency of 82.50/82.91, higher efficiency than the specified standard of 80/80. Level of satisfaction with learning about Inventories Using the project as a base of 3rd year vocational certificate students, Khunhan Vocational College The results of the analysis of satisfaction with teaching and learning on the subject of inventories using projects as a base. Of the 3rd year Vocational Certificate level students at Khunhan Vocational College, it was found that the overall average was 4.56, standard deviation 0.53, in the highest level.